New Antifungal Agents: Synthesis, Characterization and Biological Activity of Some Mannich Bases Derived from 2-Mercaptobenzothiazole - Gutierrez, Carolina Guadalupe (2023)
A series of new 3-[(amino)methyl]-1,3-benzothiazole-2-thione 4(a-l) were synthesized by Mannichreaction from formaldehyde, aliphatic or aromatic amines and 2-mercaptobenzothiazole. All synthesized compounds were in good agreement with elemental and spectral data (1H NMR and mass spectroscopy) and were evaluated for in vitro antifungal activity by agar well diffusion method. Fluconazole was included in the assays as a commercially available reference compound. Four fungal strains were used to perform the study: Cladosporium cladosporioides, Aspergillus niger ATCC 16404, Botrytis sp. and Rhizopus sp. Compounds 4a-c, 4e-g, 4i and 4l were found to be active against the four moulds mentioned, due to the presence of inhibitory halo. 4h was active in case of C. cladosporioides. Compounds 4d, 4j and 4k did not show inhibition against fungi used for the test. Fluconazole showed biological activity against Aspergillus niger ATCC 16404 and Botrytis sp. Therefore, 8 of the 12 synthesized substances would be considered as promising products to the treatment of fungal diseases.